Innovative behavior and the Chinese enterprise survival risk: An empirical research - Zongke Bao (China Finance and Economic Review, 2016)
The Chinese firms face enormous survival risk in economic transition, with an average life expectancy of less than 4 years. We employ propensity score matching and Cox model to overcome the sample bias and right censoring, investigate the inhibitory effect of innovation to firm survival risk both static and dynamic dimensions. There are the following findings from this paper. First, compared with the non-innovative enterprises, the innovative enterprises own higher competence of risk resistance, as innovative activities can release about 12% survival risk for enterprises and extend their survival time by 0.84 year. Second, the influence of innovative intensity on the enterprises' survival probability presents the characteristics of being non-stationary rather than proportional, which means the stronger innovative intensity will not necessarily bring more obvious inhibition effect. Third, the characteristics of being different within enterprises will change the effect of innovation activity on inhibiting survival risk. The survival incremental effect of large-scale enterprises with high productivity through innovative activities is more apparent, as innovative activities help to relieve the agglomeration of survival risk from those long-established enterprises. But those enterprises with financing limit are not suitable for innovative activities.
Keywords: D21; L25; L60; 330; Innovative behavior; Survival risk; Cox risk model; Treatment effect